LGBTQ Employee Groups: Who Are They Good For? How Are They Organized? - Rod P. Githens; Steven R. Aragon (Adult Education Research Conference, 2007)
LGBTQ employees seek workplace change through formal and informal groups. Some groups emphasize broader social change and others focus on organizational performance. We provide the social and historical background of these groups and provide a framework for understanding their goals and aims.